Lagrange multiplier‐based error compensation of heterodyne interferometer. Issue 20 (13th September 2016) - Lee, K.; Pyo, Y.; You, K.
Abstract : The heterodyne laser interferometer is an ultra‐precise measurement apparatus. However, its susceptibility to environmental error is an obstacle to improve its nanometre‐scale measurement accuracy. To minimise the environmental error factor, a compensation algorithm using a Lagrange multiplier method is proposed. The improved accuracy of the proposed method was verified by means of experiments using nanometre‐scale measurements of a capacitive displacement sensor.